Kajian literatur identifikasi dan pemahaman tentang kontaminasi mikroplastik di biosfer - Ratnaningsih, Wahyu; Prayogo, Wisnu; Saputra, Andri; Shabrina, Husna Muizzati (Hasanuddin University, 2025)
Microplastics are plastic particles with a size less than 5 mm which pose a growing concern in terms of ecotoxicology in aquatic environments and human health. Despite the widespread presence of microplastic pollution in land, water, and air, these environments are often viewed in isolation, although they are intricately interconnected. This study endeavors to examine the existing scientific literature pertaining to microplastic research across various environmental compartments and identify research gaps to shape future priorities. Scientific papers addressing microplastic pollution, published between 2014 and 2023, have been identified in the Web of Science database. Original research articles categorized under Environmental Sciences, Marine/Freshwater Biology, Toxicology, Multidisciplinary Sciences, Environmental Studies, Oceanography, Limnology, and Ecology in the Web of Science are chosen for a detailed investigation into microplastic research in seas, estuaries, rivers, lakes, soil, and the atmosphere. The selected papers for seas, estuaries, rivers, and lakes are further categorized based on (i) occurrence and characterization, (ii) uptake by and effects on organisms, and (iii) issues related to fate and transport. The findings indicate that, despite significant scientific research on marine microplastics, our understanding of the extent of microplastic pollution in continental environments, including rivers, lakes, soil, and air, as well as the associated environmental interactions, remains limited.